2015
DOI: 10.1177/0040517515599739
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the accessibility of starch size and cellulose to enzymes in raw cotton woven fabric by air-plasma pretreatment

Abstract: 6 7 In this paper raw cotton fabric was pre-treated with non-thermal atmospheric air-plasma and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Our earlier investigations of cellulose fibers by AFM showed that a 30 s long plasma treatment caused a slight, but detectable roughness increase. However, the statistical significance could not be unequivocally ascertained.…”
Section: Introductionmentioning
confidence: 88%
“…Our earlier investigations of cellulose fibers by AFM showed that a 30 s long plasma treatment caused a slight, but detectable roughness increase. However, the statistical significance could not be unequivocally ascertained.…”
Section: Introductionmentioning
confidence: 88%
“…The modified starch obtained using LIU treatment may be more suitable for specific applications requiring enzymatic modification. 29 Conversely, LIU has the potential to elevate starch solubility by disrupting its granular structure. 20 Starch is insoluble in water due to the presence of a compact granular structure that restricts water access to the interior of the granules.…”
Section: Ultrasound-assisted Techniques For Starch Modificationmentioning
confidence: 99%
“…Treatment time is also a key parameter and not easy to determine. Some authors use a few seconds of treatment [98], claiming that longer treatment times did not produce a more significant effect, or the sample was damaged seriously [99], while others choose very long treatment times, sometimes up to 1 hour, without the destruction of the sample [97]. It is very difficult to compare the different treatments, as in most cases, the plasmas are different even if produced in the same device.…”
Section: Characterization Of the Effectiveness Of Plasma Treatmentmentioning
confidence: 99%